Prediseño de 2 sistemas de tratamiento de agua potable para la población rural de la Vereda Yayata del (2023)
The present work contains the preliminary design of two alternatives for compact drinking water treatment systems in Vereda Yayatá, located in the municipality of Silvania, Cundinamarca. These alternatives were developed based on an arithmetic calculation model and address the water consumption needs of the population.